Serum, but not monocyte macrophage foam cells derived from low HDL-C subjects, displays reduced cholesterol efflux capacity - Nakanishi, Shuhei; Vikstedt, Riikka; Söderlund, Sanni; Lee-Rueckert, Miriam; Hiukka, Anne; Ehnholm, Christian; Muilu, Mikko; Metso, Jari; Naukkarinen, Jussi; Palotie, Leena; Kovanen, Petri T.; Jauhiainen, Matti; et al. (Journal of lipid research, 2009)
The main antiatherogenic function of HDL is to promote the efflux of cholesterol from peripheral cells and transport it to the liver for excretion in a process termed reverse cholesterol transport. The aim of this study was to evaluate the cholesterol efflux capacity in low- and high-HDL subjects by utilizing monocytes and serum from 18 low-HDL and 15 high-HDL subjects. Low and high HDL levels were defined, respectively, as HDL ≤10th and HDL ≥90th Finnish age/sex-specific percentile. Cholesterol efflux from [3H]cholesterol-oleate-acetyl-LDL-loaded monocyte-derived macrophages to standard apolipoprotein A-I (apoA-I), HDL2, and serum was measured. In addition, cholesterol efflux from acetyl-LDL-loaded human THP-1 macrophages to individual sera (0.5%) derived from the study subjects was evaluated. Cholesterol efflux to apoA-I, HDL2, and serum from macrophage foam cells derived from low- and high-HDL subjects was similar. The relative ABCA1 and ABCG1 mRNA expression levels in unloaded macrophages, as well as their protein levels in loaded macrophage foam cells, were similar in the two study groups. Cholesterol efflux from THP-1 foam cells to serum recovered from high-HDL subjects was slightly higher than that to serum from low-HDL subjects (P = 0.046). Cholesterol efflux from THP-1 macrophages to serum from study subjects correlated with serum apoB (P = 0.033), apoA-I (P = 0.004), apoA-II (P < 0.0001), and the percentage of apoA-I present in the form of preβ-HDL (P = 0.0001). Our data reveal that macrophages isolated from either low- or high-HDL subjects display similar cholesterol efflux capacity to exogenous acceptors. However, sera from low-HDL subjects have poorer cholesterol acceptor ability as compared with sera from high-HDL subjects.